Research as a Standard of Care in the PICU*. Issue 1 (January 2016) - Zimmerman, Jerry J.; Anand, Kanwaljeet J. S.; Meert, Kathleen L.; Willson, Douglas F.; Newth, Christopher J. L.; Harrison, Rick; Carcillo, Joseph A.; Berger, John; Jenkins, Tammara L.; Nicholson, Carol; Dean, J. Michael
Abstract : Objectives: Excellence in clinical care coupled with basic and applied research reflects the maturation of a medical subspecialty, advances that field, and provides objective data for identifying best practices. PICUs are uniquely suited for conducting translational and clinical research. In addition, multiple investigations have reported that a majority of parents are interested in their children's participation in clinical research, even when the research offers no direct benefit to their child. However, such activity may generate ethical conflict with bedside care providers trying to acutely identify the best approach for an individual critically ill child. Ultimately, this conflict may diminish enthusiasm for the generation of scientific evidence that supports the application of evidence-based medicine into PICU clinical standard work. Accordingly this review endeavors to provide an overview of current state PICU clinical research strengths, liabilities, opportunities, and barriers and contrast this with an established pediatric hematology-oncology iterative research model that constitutes a learning healthcare system. Data Sources, Data Extraction, and Data Synthesis: Narrative review of medical literature published in English. Conclusions: Currently, most PICU therapy is not evidence based. Developing a learning healthcare system in the PICU integrates clinical research into usual practice and fosters a culture of evidence-based learning and continual care improvement. As PICU mortality has significantly decreased, identification and validation of patient-centered, clinically relevant research outcome measures other than mortality is essential for future clinical trial design. Because most pediatric critical illness may be classified as rare diseases, participation in research networks will facilitate iterative, collaborative, multiinstitutional investigations that over time identify the best practices to improve PICU outcomes. Despite real ethical challenges, critically ill children and their families should have the opportunity to participate in translational/clinical research whenever feasible. Abstract : Supplemental Digital Content is available in the text.